The Role Of The Lampung Provincial Financial Audit Agency In Determining State Losses - Aditya Bardawansyah (Fakultas Hukum Universitas Lampung, 2020)
The Supreme Audit Agency is the institution that has the authority to calculate and determine state losses, but in its implementation, there are still requests for calculating state financial losses that have not been implemented. This study uses a normative juridical approach. Then it is analyzed qualitatively so that the results are obtained: First, the BPK-RI Representatives of Lampung Province have been given the trust by law enforcement officials to calculate and determine state losses, and the State Financial Loss Calculation Result Report submitted by BPK-RI is used as evidence in court as evidence regarding there is a state loss. Second, the methods used by BPK-RI in calculating state financial losses are by using several methods, namely the apple to apple comparison method, the production cost method, the comparison method between the contract value and the market price, the total loss, and the real cost method. The method used by BPK-RI Representatives of Lampung Province in calculating state losses is by using the simple cost method. This method is used by calculating the difference between the funds spent by the state to obtain goods/services from third parties, compared to the value of real expenditures incurred by the implementing party to provide goods/services to the state according to the agreed